Isolation and identification of BRV G6P[1] strain in Heilongjiang province, Northeast China - Li, Chunqiu; Wang, Xiaoran; Zhu, Qinghe; Sun, Dongbo (Frontiers in Veterinary Science, 2024)
Bovine rotavirus (BRV) is the main cause of acute gastroenteritis in calves, resulting in significant economic losses to the cattle industry worldwide. Additionally, BRV has multiple genotypes, which could enable cross-species transmission, thereby posing a significant risk to public health. However, there is a problem of multiple genotypes coexisting in BRV, and the cross-protection effect between different genotypes of rotavirus strains is not effective enough. Therefore, mastering clinical epidemic genotypes and using epidemic genotype strains for vaccine preparation is an effective means of preventing and controlling BRV. In this study, BRV strain DQ2020 in MA104 cells was identified by transmission electron microscopy (TEM), reverse transcription polymerase chain reaction (RT-PCR), and colloidal gold immunochromatographic test strips. The whole genome of BRV strain DQ2020 was sequenced and pathogenicity in suckling mice was assessed. The results showed that after 10 passages in MA104 cells, BRV strain DQ2020 induced cytopathic effects. Wheel-shaped virus particles (diameter, ~80 nm) were observed by TEM. A target band of 382 bp was detected by RT-PCR, a positive band was detected with the colloidal gold immunochromatographic test strips, and significant green fluorescence was observed by indirect immunofluorescence (IFA). The highest median tissue culture infectious dose of strain DQ2020 after 9 passages in MA104 cells was 10−4.81 viral particles/0.1 mL. Based on phylogenetic analysis of 11 gene fragments, the genotype of BRV strain DQ2020 was G6-P[1]-I2-R2-C2-M2-A11-N2-T6-E2-H3, confirming transmission of the G6-P[1] genotype in Chinese cattle herds. Further analysis showed that the isolated strain was a reassortant of bovine (VP7, VP6, NSP3, and NSP5), human (VP4, VP1, VP2, VP3, NSP2, and NSP4), and ovine (NSP1) rotaviruses. BRV strain DQ2020 caused damage to the intestinal villi of suckling mice and diarrhea, confirming pathogenicity. In summary, this study identified a reassortant strain of bovine, human, and ovine rotavirus that is pathogenic to lactating mice, and conducted whole genome sequence analysis, providing valuable insights for the genetic evolution of the virus and the development of vaccines.